2015
DOI: 10.1007/s11998-014-9644-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of inhibitor anion-intercalated layered double hydroxide host films on aluminum alloy 2024 and their anticorrosion properties

Abstract: ZnAl layered double hydroxide (LDH) host films have been synthesized on aluminum alloy 2024 substrate via a facile crystallization method, and then intercalated with different corrosion inhibitor anions (vanadate, molybdate, and 2-mercaptobenzothiazolate). The structures, compositions, and morphologies of the as-synthesized films before and after the anionexchange reaction were characterized by means of glancing-angle X-ray diffraction, Fourier transform infrared, X-ray photoelectron spectroscopy, and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 40 publications
(41 reference statements)
3
21
0
Order By: Relevance
“…According to Figure c, the curved platelike LDH microcrystals were perpendicular to the substrate and covered the entire substrate surface. This nestlike microstructure is in good accordance with the reported literature . After treatment with sodium laurate, the morphology of the ZnAl–LDHs film transformed from a packed sheet to flowerlike structure.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to Figure c, the curved platelike LDH microcrystals were perpendicular to the substrate and covered the entire substrate surface. This nestlike microstructure is in good accordance with the reported literature . After treatment with sodium laurate, the morphology of the ZnAl–LDHs film transformed from a packed sheet to flowerlike structure.…”
Section: Resultssupporting
confidence: 92%
“…Researchers have intercalated a large variety of inhibitor ions into the LDH films such as vanadates, molybdates, 2-mercaptobenzothiazolates, and 8-hydroxyquinoline, based on the large interlayer space of LDHs. The results indicate that the inhibitor-loaded LDHs present better corrosion protection effect for the Al substrate in comparison with those without them. In addition to intercalating inhibitor anions into LDHs, researchers also modified them with low-surface-energy substances such as fluoroalkylsilane, aliphatic carboxylate, or the corresponding acid to obtain a superhydrophobic surface. When the superhydrophobic surface was immersed in solution, an “air valley” film was formed on the surface, acting as a strong physical barrier against water molecules and aggressive ions.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from Figure 4a1–a3,b1–b3, both the LDH platelets of ZnAl‐LDH and ZnAl‐LDH‐lignin grew perpendicularly on the AA 7075 surface, indicating typical morphology of in situ grown LDH films on metal substrate. [ 42 ] It can be seen that the surface structure of LDH platelets remained almost as intact as that before modification, indicating that the modification process in alkali solution did not lead to the destruction of the structure. It is worth noting that ZnAl‐LDH‐lignin film was more compact and denser than ZnAl‐LDH, which was probably caused by the positive influence of the modification process.…”
Section: Resultsmentioning
confidence: 97%
“…Figure D wo reveals that the scribe of AA6014WO is covered with a layer with the morphology of a hydrated aluminium oxide, which can indicate that the substrate is affected by corrosion. In contrast to these samples, all the scribes of the alloy samples coated with the Li‐carbonate loaded coatings were covered by a layer with a polycrystalline morphology, featuring intersecting plate‐like crystals that is commonly observed for layered double hydroxide compounds generated on aluminium and is typical for the protective layer generated from the lithium‐leaching coating technology . The size of the crystals varies per alloy, but it is evident that the formation of these layers is a result from the active protective nature of the lithium‐leaching coatings.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that all scribes are covered with a layer, but no severe corrosion was observed at this magnification. commonly observed for layered double hydroxide compounds generated on aluminium 6,17,18 and is typical for the protective layer generated from the lithium-leaching coating technology. 9,19 The size of the crystals varies per alloy, but it is evident that the formation of these layers is a result from the active protective nature of the lithium-leaching coatings.…”
Section: Detailed Morphological Observations In the Scribed Defect mentioning
confidence: 85%